The Role of Protocollary Management in Realizing Harmonization Between Bureaucracy in the Government of the Riau Islands Province - Careca Ady Guna; Rumzi Samin; Fitri Kurnianingsih (Jurnal Manajemen Publik dan Kebijakan Publik (JMPKP), 2026)
Protocol is a crucial aspect in the administration of regional government, especially in supporting the smooth running of the official agenda of the Governor of the Riau Islands as regional head and representative of the central government in the region. The role of protocol is not only limited to regulating spatial planning and ceremonies, but also functions to maintain the image of the institution, strengthen communication between agencies, and ensure respect for various local customs. This research aims to analyze the role of management in implementing the Riau Islands Governor's protocol and identify the challenges faced. This research uses a qualitative descriptive method. This research discusses the transformation of protocol management within the Riau Islands Provincial Government which no longer merely carries out the technical function of organizing ceremonial events, but has developed into a strategic instrument in supporting the effectiveness of government communications, strengthening the institutional image, and maintaining smooth cross-bureaucratic coordination. In conclusion, the role of protocol is not only focused on the technical planning of ceremonial events, but has also developed into an important element in managing government communications, ensuring smooth coordination between bureaucracies, and forming a positive image of local government.